MBL-2 polymorphisms (codon 54 and Y-221X) and low MBL levels are associated with susceptibility to multi organ dysfunction in P. falciparum malaria in Odisha, India - Das, Bidyut K.; Panda, Aditya K. (Frontiers in Microbiology, 2015)
Background Mannose binding lectin, a plasma protein protects host from virus, bacteria and parasites. Deficiency in MBL levels has been associated with susceptibility to various infectious diseases including P. falciparum malaria. Common MBL polymorphisms in promoter and coding regions are associated with decrease in plasma MBL levels or production of deformed MBL, respectively. In the present study, we hypothesized that MBL2 variants and plasma MBL levels could be associated with different clinical phenotypes of severe P. falciparum malaria. Methods A hospital based study was conducted in eastern Odisha, India which is endemic to P. falciparum malaria. Common MBL-2 polymorphisms (codon 54, H-550L and Y-221X) were typed in 336 cases of severe malaria (SM) [94 cerebral malaria (CM), 120 multi-organ dysfunction (MOD), 122 non-cerebral severe malaria (NCSM)] and 131 un-complicated malaria patients (UM). Plasma MBL levels were quantified by ELISA. Results Severe malaria patients displayed lower plasma levels of MBL compared to uncomplicated falciparum malaria. Furthermore,on categorization of severe malaria patients into various subtypes, plasma MBL levels were very low in MOD patients compared to other categories. Higher frequency of AB genotype and allele B was observed in MOD compared to UM (AB genotype: P=0.006; B allele: P=0.008). In addition, prevalence of YX genotype of MBL Y-221X polymorphism was also statistically more frequent in MOD case than UM (P=0.009). Conclusions The observations of the present study reveal that MBL-2polymorphisms (codon 54 and Y-221X) and lower plasma MBL levels are associated with increased susceptibility to multi organ dysfunctions in P. falciparum malaria.